Implementation Of Group Guidance Program Management in Improving Cooperation Learning - Abdurrahman Abdurrahman; Yusuf Hadijaya; Muhammad Latif Sipahutar (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to describe the implementation of group counseling guidance management in increasing cooperative learning at SMPT IT Al Afkari Batang Kuis. This research method is descriptive qualitative using two data collection techniques: interviews and documentation. Data analysis techniques are data reduction, data display, conclusion, and data verification. The results show Principals are very supportive and have an important role in the process of BK service activities, such as providing a budget for BK activities themselves. The school principal is involved in the process of BK service activities and also motivates students. Counseling teachers in carrying out their duties play an active role in BK activities including group guidance activities. BK teachers carry out the process of group guidance services according to the conditions and needs of the students. In the process of implementing group guidance services carried out by BK teachers at SMP IT Al-Afkari, it is intended that students can improve collaboration in learning better with other students. Through the service process group guidance, a lot of changes occur in individual students, one of which is learning with the mediocre, to be better than before. Increasing student learning cooperation with other students through group guidance services with the material increasing cooperation with fellow students and improving the way students learn. In addition to providing material, researchers also provide various forms of games that are characterized by the intimacy between members in the group so that they are able to work together well in learning.